Protein-losing enteropathy. Issue 3 (May 2020) - Elli, Luca; Topa, Matilde; Rimondi, Alessandro
Abstract : Purpose of review: The present review offers its readers a practical overview of protein-losing enteropathy, particularly with regard to diagnostic and therapeutic approaches. The aim is to support clinicians in their daily practice with a practical tool to deal with protein-losing enteropathy. Recent findings: The literature covering protein-losing enteropathy does not appear to be quite recent and also guidelines are scanty. The main innovations during the last decade probably regard the introduction of enteroscopic techniques in the diagnostic flowchart. The use of video-capsule and device-assisted enteroscopy has enabled the direct exploration of the small bowel and the identification of the damage causing the loss of proteins from the gastrointestinal tract. Other innovations are to do with the therapies of the disorder underlying protein-losing enteropathy, although the support with nutritional supplementation are the direct remedies to tackle the protein loss. Summary: Protein-losing enteropathy represents an important clinical aspect of different gastrointestinal and extra-intestinal diseases. An established flowchart is still unavailable, but the use of enteroscopy has deeply changed the modern diagnostic approach. Nutritional support and therapy of the underlying disease are pivotal to patients' management.